Visual acuity outcomes and complications after intraocular lens exchange: an IRIS® registry (Intelligent Research in Sight) analysis - Son, Hyeck Soo; Chang, David F.; Li, Charles; Liu, Lynn; Zafar, Sidra; Lum, Flora; Woreta, Fasika A. (Ophthalmology, 2024)
Purpose - To assess risk factors for worse visual acuity (VA) outcomes after intraocular lens (IOL) exchange, and the most common postsurgical complications. - Design - Retrospective cohort study. - Participants - Eyes from patients 18 years of age and older in the IRIS® Registry (Intelligent Research in Sight) that underwent IOL exchange in the United States between 2013 and 2019. - Methods - Vision improvement compared with baseline was determined at 1 year after surgery. A multivariable generalized estimating equation model adjusting for demographic factors and baseline vision was used to identify factors associated with VA worse than 20/40 at 1 year. - Main Outcome Measures - Visual outcomes and postoperative complications after lens exchange. - Results - A total of 46 063 procedures (n = 41 925 unique patients) were included in the analysis. Overall, VA improved from a mean ± standard deviation (SD) of 0.53 ± 0.58 logarithm of the minimum angle of resolution (logMAR; Snellen equivalent, 20/70) before surgery to a mean ± SD of 0.31 ± 0.40 logMAR (Snellen equivalent, 20/40) at 1 year. Among eyes with VA recorded at both baseline and 1 year after surgery, 60.5% achieved VA of 20/40 or better at 1 year. Vision of worse than 20/40 at 1 year was associated with greater age (odds ratio [OR], 1.16 per 5-year increase; 95% confidence interval [CI], 1.14-1.18) and higher logMAR baseline VA (OR, 1.14 per 0.1-logMAR increase; 95% CI, 1.14-1.15), as well as Black or African American (OR, 1.96; 95% CI, 1.68-2.28), Hispanic (OR, 1.82; 95% CI, 1.59-2.08), and Asian (OR, 1.48; 95% CI, 1.21-1.81) race or ethnicity versus White race, Medicaid (OR, 1.78; 95% CI, 1.40-2.25) versus private insurance, smoking history (OR, 1.22; 95% CI, 1.11-1.35), and concurrent anterior (OR, 1.65; 95% CI, 1.51-1.81) and posterior (OR, 1.53; 95% CI, 1.41-1.66) vitrectomy versus no vitrectomy. Female sex was associated with better VA at 1 year. At 1 year, epiretinal membrane (10.9%), mechanical lens complication (9.4%), and dislocation of the replacement lens (7.1%) were the most common complications. - Conclusions - In this large national cohort, the annual number of IOL exchanges rose steadily over time. Vision improved in 60.2% of patients; worse visual outcomes were associated with greater age, worse baseline vision, Black race, Hispanic ethnicity, Medicaid insurance, smoking, and concurrent vitrectomy. Epiretinal membrane was the most common complication. - Financial Disclosure(s) - Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.
Online verfügbar: 18. Oktober 2023, Artikelversion: 20. März 2024
Gesehen am 08.10.2024